Symptoms in a population of contact lens and noncontact lens wearers under different environmental conditions - González-Méijome, José Manuel (2007)
None of the authors has a commercial or financial interest in the instruments or materials used in the study. The authors wish to thank the assistance of AP Almeida, AP Costa, A, Fernandes, A Teixeira, C Marques, C Pinho and J Matos for their assistance in data acquisition, and Dr. Ana Costa from the program of Support to the Edition of Scientific Papers at the University of Minho for help with English editing of the manuscript.